ASSESSMENT OF THE GENOTOXIC AND MUTAGENIC EFFECT OF AL-TAIF POMEGRANATE (PUNICA GRANATUM L) PEEL EXTRACT ALONE AND COMBINED WITH MALATHION AND ATRAZINE PESTICIDES IN LIVER OF MALE ALBINO MICE - Hussien, Nahed A; M Abd El-azez, Asmaa; Z. Hamza, Reham (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT In our previous studies, we report the antioxidant, hepatoprotective and nephroprotective potential of of Al-Taif Pomegranate (Punica granatum L) extracts against toxicity induced by Malathion (Mal) and Atrazine (Atra) pesticides in male albino mice. Hereby, we assess the genotoxic and mutagenic potential of Al-Taif Pomegranate (P. granatum L) peel extract (PPE) alone and combined with Atra and Mal pesticides in the liver of male albino mice. Our results report PPE genotoxicity and its failure to significantly decrease the genotoxic effect of the pesticides Mal and Atra. Genotoxic potential was reported by using Comet assay, in which fifty isolated comets were randomly selected and used to measure tail length, % DNA of tail and tail moment for each group in comparison with the negative control group. Moreover, PPE combined (Mal and Atra) groups show DNA point of mutation in P53 exon 5, that was detected by the highly sensitive and accurate assay single-strand conformation polymorphism (SSCP), represented by an extra third band in comparison with the negative control group. This mutation was not detected by direct sequencing, means that it is a low-frequency mutation. In conclusion, our results report Al-Taif PPE as a genotoxic extract and mutagenic in combination with Mal and Atra pesticides. Moreover, the present results also confirm the sensitivity of SSCP technique in detection of point of mutation in comparison to direct sequencing. Keywords: Malathion, Atrazine, Pomegranate peel extract, Mutagenic, Genotoxic.